Severe Protein C Deficiency in Congenital Thrombotic Disease – Description of an Immunoenzymological Assay for Protein C Determination - Soria, J; Soria, C; Samama, M; Nicolas, G; Kisiel, W (Thrombosis and Haemostasis, 1985)
An immunoenzymatic assay (ELISA) is described for the quantitative assay of protein C in plasma. This technique allows a safe, reliable, and sensitive assay of protein C, and is easily used for routine investigation. Using this technique, a protein C deficiency (0.16 U/ml) was discovered in a 16 year old patient with a history of very severe thrombotic disease. Protein C deficiency was also discovered in his mother (0.62 U/ml) and father (0.50 U/ml). We therefore suggest that this case could represent a homozygous deficiency of protein C.
Keywords: Protein C; Protein C deficiency; Thrombotic disease